2012
DOI: 10.1371/journal.pone.0043369
|View full text |Cite
|
Sign up to set email alerts
|

Novel Somatic Mutations to PI3K Pathway Genes in Metastatic Melanoma

Abstract: BackgroundBRAFV600 inhibitors have offered a new gateway for better treatment of metastatic melanoma. However, the overall efficacy of BRAFV600 inhibitors has been lower than expected in clinical trials, and many patients have shown resistance to the drug’s effect. We hypothesized that somatic mutations in the Phosphoinositide 3-Kinase (PI3K) pathway, which promotes proliferation and survival, may coincide with BRAFV600 mutations and contribute to chemotherapeutic resistance.MethodsWe performed a somatic mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 38 publications
(48 reference statements)
2
67
0
Order By: Relevance
“…This gene serves a role in cell growth, differentiation, proliferation, motility, survival and intracellular transport, and its route is associated with the progression of melanoma (37,38). The PIK3R5 gene is associated with inhibition of autophagy (promoting tumor growth) (39) and certain authors have suggested that autophagy also works as a cytoprotective mechanism (40).…”
Section: Discussionmentioning
confidence: 99%
“…This gene serves a role in cell growth, differentiation, proliferation, motility, survival and intracellular transport, and its route is associated with the progression of melanoma (37,38). The PIK3R5 gene is associated with inhibition of autophagy (promoting tumor growth) (39) and certain authors have suggested that autophagy also works as a cytoprotective mechanism (40).…”
Section: Discussionmentioning
confidence: 99%
“…In melanomas, activation of the PI3K pathway can act in concert with the RAS/ RAF pathway to promote melanoma tumorigenesis and metastasis (14,40). The PI3K signaling pathway is often upregulated in melanoma (3) through activating mutations of the PIK3CA gene encoding the p110␣ catalytic subunit (13,41,45), by loss-of-function mutations in PTEN, which have been detected in 10 to 30% of melanomas (50), by epigenetic silencing of PTEN expression (57), and by activation of AKT3 (46). The ability of PI3K to regulate expression of Brn-2, a transcription factor that can downregulate MITF expression to promote an invasive phenotype in vitro and in vivo (2,4,19,42,48), fits nicely with a role for PI3K signaling in promoting highly aggressive melanomas in a BRAF, Pten Ϫ/Ϫ mouse melanoma model (14).…”
Section: Discussionmentioning
confidence: 99%
“…A report that analyzed 68 metastatic melanomas showed that 41% presented a mutation in this pathway [102]. Besides 3% of metastatic melanomas presents activating mutation of PI3K and 5-20% of late-stage melanoma present mutations that leads to PTEN loss, which is the protein most commonly mutated in this pathway [1].…”
Section: Pi3kmentioning
confidence: 99%